2012
DOI: 10.1038/npp.2012.76
|View full text |Cite|
|
Sign up to set email alerts
|

Yohimbine Depresses Excitatory Transmission in BNST and Impairs Extinction of Cocaine Place Preference Through Orexin-Dependent, Norepinephrine-Independent Processes

Abstract: The alpha2 adrenergic receptor (a 2 -AR) antagonist yohimbine is a widely used tool for the study of anxiogenesis and stress-induced drug-seeking behavior. We previously demonstrated that yohimbine paradoxically depresses excitatory transmission in the bed nucleus of the stria terminalis (BNST), a region critical to the integration of stress and reward pathways, and produces an impairment of extinction of cocaine-conditioned place preference (cocaine-CPP) independent of a 2 -AR signaling. Recent studies show y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 71 publications
(111 reference statements)
0
14
0
Order By: Relevance
“…However, while PVN-CRF neurons are mostly glutamatergic, BNST-CRF neurons are primarily GABAergic [30], thereby offering diverse mechanisms for Hcrt modulation of stress circuits. In one recent study, slice application of Hcrt to neurons in the CRF-enriched dorsolateral BNST (dlBNST) of adult mice depressed excitatory post-synaptic currents (EPSCs) in a HcrtR1-specific manner [31]. Interestingly, these effects on excitatory dlBNST transmission mimicked those of yohimbine, the alpha-2 NE receptor antagonist known to reinstate operant alcohol-seeking through a HcrtR1-mediated mechanism [32].…”
Section: Hypocretin Modulation In the Bnst And Amygdalamentioning
confidence: 99%
See 1 more Smart Citation
“…However, while PVN-CRF neurons are mostly glutamatergic, BNST-CRF neurons are primarily GABAergic [30], thereby offering diverse mechanisms for Hcrt modulation of stress circuits. In one recent study, slice application of Hcrt to neurons in the CRF-enriched dorsolateral BNST (dlBNST) of adult mice depressed excitatory post-synaptic currents (EPSCs) in a HcrtR1-specific manner [31]. Interestingly, these effects on excitatory dlBNST transmission mimicked those of yohimbine, the alpha-2 NE receptor antagonist known to reinstate operant alcohol-seeking through a HcrtR1-mediated mechanism [32].…”
Section: Hypocretin Modulation In the Bnst And Amygdalamentioning
confidence: 99%
“…In a separate study, slice application of Hcrt depolarized a subset of neurons in the posterior BNST of adult rats [33]. These effects contrast with those observed in mice [31], but are consistent with the ability of intra-BNST Hcrt to increase anxiety-like behavior via NMDA receptor activation [33]. Even a single subregion of the BNST can display tremendous cellular heterogeneity [30], and Hcrt's modulatory actions undoubtedly vary across cell types, highlighting the need for detailed studies of Hcrt's effects in genetically- or physiologically-defined BNST neurons.…”
Section: Hypocretin Modulation In the Bnst And Amygdalamentioning
confidence: 99%
“…OX-A infusions into the BNST produce anxiety like responses as measured by social interaction test and elevated plus maze test and the effect is mediated by NMDA receptors (107). A recent study also demonstrated that yohimbine activates orexinergic responses, but not adrenergic receptor activity, and depressed excitatory neurotransmission in the BNST that contributed to reinstatement of extinguished cocaine CPP (108). Thus the orexinergic system is involved in mediating stress-induced drug-seeking behavior as it recruits multiple brain regions involved in processing stressful stimuli and addictive behaviors.…”
Section: Role Of Orexins In Addictionmentioning
confidence: 99%
“…Yohimbine and atipamezole show equal affinities at all three receptor subtypes, but atipamezole has a 200-fold greater selectivity than yohimbine for the a2AR over the a1AR (Schwartz and Clark, 1998). Because yohimbine interacts with a number of non-noradrenergic systems in addition to acting at the a2AR, its effects should be interpreted with caution (Feuerstein et al, 1985;Millan et al, 2000;Conrad et al, 2012).…”
Section: Pharmacologic Compounds Targeting Adrenergic Receptorsmentioning
confidence: 99%
“…However, when the data were reanalyzed to control for initial preference, a high dose of prazosin accelerated extinction in animals with a high initial preference score (Bernardi and Lattal, 2012b). Yohimbine impaired the extinction of cocaine CPP, although this effect was not replicated with a selective a2AR antagonist and may be mediated by orexin rather than NE (Davis et al, 2008;Conrad et al, 2012).…”
Section: Place Preference and Aversionmentioning
confidence: 99%